Experimental and Numerical Studies of the Wave-Induced Responses of a River-to-Sea Ship - Wang, Yiwen; Wu, Weiguo; Guedes Soares, C. (Journal of marine science and application, 2018)
The ship motions and wave-induced loads of a new type of river-to-sea ship are investigated experimentally and numerically. A river-to-sea ship is an unconventional type of container ship characterized by high breadth to draft ratio and low length to breadth ratio, which makes it more prone to hydroelasticity than conventional ships of the same size. A segmented model was tested under two loading conditions, namely, ballast and loaded conditions, to determine the vertical motions and wave-induced loads under each condition. Results are compared with numerical simulations in the frequency domain. The wave-induced responses are calculated by a nonlinear time domain code at each time step. The response amplitude operators of vertical ship responses in regular waves are analyzed, and the wave-induced responses are consistent with the experimental results.